Disain dan uji coba praktikum masa pendemi menggunakan bahan dan alat dapur pada materi indikator asam basa - kuncoro hadi (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
Design and trial of the covid 19 pandemic practicum using kitchen materials and tools on acid-base indicator materials have been implemented using R&D approaches. in this research using five stages of development. The results showed that the average value of the practicum guide in terms of material, media and teacher assessment was 4.96 respectively; 4.87; 4.76. With the percentage values obtained respectively 99.2%, 97.4%, and 95.2%. The practicum guide can be used as a reference for students in practicum and can be used as a reference for teachers in guiding students.Keywords: acids and bases, indicators, kitchen materials and tools, R&D research